El acoso laboral desde la óptica del derecho a la salud integral - Cuasapaz Aguirre, Jessica Mariana (2023)
The present dissertation seeks to study about workplace harassment from the view of integrate health, making an analysis, from labor rights, work, health and human dignity, this phenomenon has been growing in the work environment to much in our country. However, the women are being more affected. The social importance of this harassment is out of controversy. There have been many studies, such as, methodologies, disciplines, approaches and diverse applications for years, assuming it as a global interest. To justify this work, we will contrast the content of the guides made, the countless behaviors of workplace harassment and field research, facilitating the approach of the forms of violence that are reproduced in workplace harassment, the current obstacles to access justice, the effectiveness of the sanctions granted by law, and integral reparation to the victims that approve their rights in the integrate health. This approach allowed us to analyze the administrative mechanisms and legal that are activated in cases of workplace harassment in Ecuador and the types of reparations provided to the victims specially related to integrate health. As a result, the solution for the reduction of labor harassment and the mechanisms to ensure the integral health of people who have been through this harassment has not been considered as a protagonist in the governmental, social, trade union and organizational agenda in our country, which has kept some cases in anonymity and in others case They are being reported but the victims have not been repaired yet. key word: integrate health, work environment, workplace harassment, integral reparation, violence;